Cost-effectiveness of extracorporeal cardiopulmonary resuscitation for adult out-of-hospital cardiac arrest: A systematic review. (September 2022) - Addison, Danielle; Cheng, Evan; Forrest, Paul; Livingstone, Ann; Morton, Rachael L.; Dennis, Mark
Abstract: Objective: The use of extracorporeal cardiopulmonary resuscitation (ECPR) for out-of-hospital cardiac arrests (OHCA) has increased dramatically over the past decade. ECPR is resource intensive and costly, presenting challenges for policymakers. We sought to review the cost-effectiveness of ECPR compared with conventional cardiopulmonary resuscitation (CCPR) in OHCA. Methods: We searched Medline, Embase, Tufts CEA registry and NHS EED databases from database inception to 2021 or 2015 for NHS EED. Cochrane Covidence was used to screen and assess studies. Data on costs, effects and cost-effectiveness of included studies were extracted by two independent reviewers. Costs were converted to USD using purchasing power parities (OECD, 2022). 1 The Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist (Husereau et al., 2022) 2 was used for reporting quality and completeness of cost-effectiveness studies; the review was registered on PROSPERO, and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Four studies met the inclusion criteria; three cost-effectiveness studies reported an incremental cost-effectiveness ratio (ICER) for OHCA compared with conventional care, and one reported the mean operating cost of ECPR. ECPR was more costly, accrued more life years (LY) and quality-adjusted life years (QALYs) than CCPR and was more cost-effective when compared with CCPR and other standard therapies. Overall study quality was rated as moderate. Conclusion: Few studies have examined the cost-effectiveness of ECPR for OHCA. Of those, ECPR for OHCA was cost-effective. Further studies are required to validate findings and assess the cost-effectiveness of establishing a new ECPR service or alternate ECPR delivery models.